Acute Cerebellitis or Postinfectious Cerebellar Ataxia? Clinical and Imaging Features in Acute Cerebellitis. (May 2020) - Yildirim, Mirac; Gocmen, Rahsan; Konuskan, Bahadir; Parlak, Safak; Yalnizoglu, Dilek; Anlar, Banu
Acute cerebellitis is a rare condition often considered within the group of acute postinfectious cerebellar ataxia despite its distinctive clinical and imaging features. We retrieved clinical, laboratory, and follow-up data of 15 children diagnosed with acute cerebellitis in our department between 2011 and 2019. There were 10 boys and 5 girls aged 3-15 years, median 9.5 years. The most common first symptoms were ataxia, vomiting, and headache. Magnetic resonance imaging (MRI) generally showed bilateral symmetrical T2 hyperintense changes with moderate swelling in the cerebellar cortex. Tonsillar herniation was present in 73.3% and obstructive hydrocephalus in 26.6%. Etiologic workup for infectious pathogens revealed Mycoplasma pneumoniae, influenza A virus, cytomegalovirus, and varicella zoster virus in 1 case each. Fourteen of 15 patients were treated with intravenous and/or oral steroids and 8 cases with intravenous immunoglobulin. No patient required surgical decompression. Neurologic examination median 12 months later revealed ataxia and dysmetria in 4 cases (27%), accompanied by memory difficulties, dysarthria or tremor. Follow-up magnetic resonance imaging (MRI; n = 12) showed diffuse cerebellar cortical T2-hyperintense signal changes in 11 cases and cerebellar atrophy in 9. The diagnosis of acute cerebellitis rather than acute postinfectious cerebellar ataxia should be considered when headache and vomiting accompany ataxia in a child. Acute cerebellitis heals with sequelae in about one-third of cases. The absence of fatalities in our series suggests early diagnosis, and steroid treatment can increase the chance of recovery. MRI results were not found to be predictive of outcome.